In vitro additive interaction between ketoconazole and antimony against intramacrophage Leishmania (Leishmania) amazonensis amastigotes. - Débora Cristina de Oliveira Nunes; Luiz Borges Bispo-da-Silva; Danielle Reis Napolitano; Mônica Soares Costa; Márcia Moura Nunes Rocha Figueira; Renata Santos Rodrigues; Veridiana de Melo Rodrigues; Kelly Aparecida Geraldo Yoneyama (PLoS ONE, 2017)
Leishmaniasis is a group of diseases caused by protozoa of Leishmania genus. The currently available treatments for this disease are expensive, present high toxicity and are associated to difficulties of healing and parasite resistance. Therefore, the development of strategies for leishmaniasis treatment is indispensable and includes reposition of existing drugs, as well as drug combination therapy. The aim of this study was to assess the nature of ketoconazole and antimony association on the cytotoxic effect against Leishmania (Leishmania) amazonensis amastigotes. The calculated mean sum of fractional 50% inhibitory concentration ([Formula: see text]ΣFIC50) was 2.54 and 1.43 for free and intracellular amastigotes, respectively, values that suggest an additive interaction between ketoconazole and antimony concerning to Leishmania toxicity only in the intramacrophage parasite form. Despite the clinical efficacy of ketoconazole-antimony combination has been shown in the literature, our study is the first to describe the nature of ketoconazole-antimony interaction against L. (L.) amazonensis amastigotes. Moreover, our results point out the need for future in vivo studies to confirm the nature of ketoconazole-antimony interaction and also to determine possible effective dosage regimens related to ketoconazole administration in association with the optimal lower dose of antimony.